Repeated Syphilis Episodes in HIV-Infected Men Who Have Sex With Men: A Multicenter Prospective Cohort Study on Risk Factors and the Potential Role of Syphilis Immunity. (12th January 2020) - Roth, Jan A; Franzeck, Fabian C; Balakrishna, Suraj; Lautenschlager, Stephan; Thurnheer, Maria Christine; Trellu, Laurence Toutous; Cavassini, Matthias; Vernazza, Pietro; Bernasconi, Enos; Braun, Dominique; Kouyos, Roger D; Battegay, Manuel; et al.
Abstract: Background: Syphilis is re-emerging globally in general and HIV-infected populations, and repeated syphilis episodes may play a central role in syphilis transmission among core groups. Besides sexual behavioral factors, little is known about determinants of repeated syphilis episodes in HIV-infected individuals—including the potential impact of preceding syphilis episodes on subsequent syphilis risk. Methods: In the prospective Swiss HIV cohort study, with routine syphilis testing since 2004, we analyzed HIV-infected men who have sex with men (MSM). Our primary outcome was first and repeated syphilis episodes. We used univariable and multivariable Andersen-Gill models to evaluate risk factors for first and repeated incident syphilis episodes. Results: Within the 14-year observation period, we included 2513 HIV-infected MSM with an initially negative syphilis test. In the univariable and multivariable analysis, the number of prior syphilis episodes (adjusted hazard ratio [aHR] per 1-episode increase, 1.15; 95% confidence interval [CI], 1.01–1.31), having occasional sexual partners with or without condomless anal sex (aHR, 4.99; 95% CI, 4.08–6.11; and aHR, 2.54; 95% CI, 2.10–3.07), and being currently on antiretroviral therapy (aHR, 1.62; 95% CI, 1.21–2.16) were associated with incident syphilis. Conclusions: In HIV-infected MSM, we observed no indication of decreased syphilis risk with repeated syphilis episodes. The extent of sexual risk behavior over time was the strongest risk factor for repeated syphilis episodes. The observed association of antiretroviral therapy with repeated syphilis episodes warrants further immunological and epidemiological investigation.